Spin-state transition of Co ion (S = 2 →S = 5/2) in hole substituted 1D chain of Ca3Co2O6. (13th July 2022) - Bisht, Gajendra Singh; Pal, D
Abstract: We have discovered spin-state transition ( S = 2 to S = 5/2) of Co ions due to Mg substitution in the Ca3 Co2 O6 apparent in the magnetic susceptibility, x-ray photoelectron spectroscopy (XPS), and first-principles study. We also examine the effect of Mg substitution on the magnetic and electronic structure of Ca3 Co2 O6 by first-principles calculations. It involves generalized gradient approximation with Coulomb interaction ( U ) in exchange–correlation energy functional. Our study shows a reasonable agreement between effective magnetic moment ( μ eff ) determined from the Curie–Weiss fit with that from the XPS analysis and first-principles calculations study. We have attributed the decrease in positive intra-chain exchange interaction constant ( J 1 / k B ) to the antiferromagnetically coupled induced Co 4+ ions ( S = 5/2) arising from the Mg 2+ ions substitution. The in-field metamagnetic transitions in the isothermal M ( H ) curves below the critical field ( H c ) have been accurately mapped and successfully explained by the change in magnetic entropy (Δ S ) calculations and Arrott plots. Electronic structure study reveals hole-type doping of Mg atom, and the Fermi level ( E F ) shifts below. Density of state and band structure calculation indicates strong hybridization between partial states of Co-3d and O-2p orbitals for the Mg-doped compound due to which the band crossing at Fermi level is observed, and a hole-type Fermi surface is formed.